Circularly Polarized Dielectric Resonator Antennas. - Chaudhary, Raghvendra Kumar; Kumar, Rajkishor; Chowdhury, Rakesh (Norwood : Artech House, 2021)
This book introduces 5 key feeding techniques such as coaxial probe, microstrip, conformal strip, aperture, and coplanar waveguide and covers different shapes of dielectric resonator antennas leading to improvement in circularly polarized (CP) performance. It introduces advancements in the field of dielectric resonator antennas and dilectric resonator antennas (DRAs). Five different types of feeding techniques (i.e. coaxial probe, microstrip, conformal strip, aperture, and coplanar waveguide) are described for obtaining CP followed by two modified shaped DRA (sector DRAs). Throughout this book, rectangular and circular with their modified shapes of the dielectric resonator are utilized, providing differing degrees of freedom as well as different variable parameters, including length, width, height, radius, aspect ratio and dielectric constant, which are tuned to obtain the desired antenna parameters.
8.4.1 Analysis of Circular Polarization in Modified Geometry -- 8.5 The Sectorization Technique in CP-MIMO Antennas -- 8.6 Summary -- References -- 9 The State of the Art in Circularly Polarized Dielectric Resonator Antennas -- 9.1 Circularly Polarized DRAs in Substrate Integrated Waveguide Technology -- 9.2 Techniques Using Circularly Polarized Liquid DRAs -- 9.3 Miscellaneous Research Areas in Circularly Polarized DRAs -- 9.4 Concluding Remarks -- References -- About the Authors -- Index.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Dielectric resonators; Antennas (Electronics); Résonateurs diélectriques.; Antennes (Électronique); Antennas (Electronics); Dielectric resonators; Electronic book